Relation Between Giving Early Weaning Food and Diarhae case in 6 month 1 Year Old Baby - rita sri; Yunita Miftahul Masita (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
Providing Early complementary feeding is feeding before the baby is 6 months old habit is not good, because it can cause the baby more often suffer from coughs, colds, simple allergies to certain foods and frequent diarrhea in infants. Of the 34 infants, 22 who received complementary feeding early and 20 had diarrhea.This study aims to determine the relationship Providing Early complementary feeding with Genesis Diarrhea in Infants Age 1-6 Months in the Work Area Health Center Binakal Bondowoso district.This study uses anaitik research with cross sectional correlation. Total population of 34 respondents mothers - mothers with babies aged 1-6 months, then using techniques cluster / random sampling taken 31 respondents to the study sampled. The results showed 61.3% of respondents have provided no Early complementary feeding of infants aged less than 6 months, 45.2% of infants with diarrhea. The results of Chi-Square test found that the χ ² count = 7.117> χ ² table = 3.481 and the value of KK = 0.432 means that there is a correlation with the level of closeness was the provision of MP-ASI Early on the incidence of diarrhea in infants aged 1-6 months in the village of Orange Sok Sok district Binakal Bondowoso district.Infants given early complementary feeding more susceptible to diarrhea than breastfed babies saja. Good cooperation between the public and health care professionals in an effort to provide education regarding the provision of complementary feeding according to age and baby's needs so as to prevent the occurrence of diarrhea.